STRATEGI NARASI VISUAL DALAM PERANCANGAN PICTURE BOOK STRESS MANAGEMENT UNTUK USIA 6-9 TAHUN - Kusumaningtyas, Ester Anggun; Rarasati, RR Annisa (Universitas Mercu Buana, 2023)
The stress experience in the childhood poses significant and enduring risks to both physical and psychological development. Stress not only adversely affects physical health but also correlates with serious issues such as suicide, psychological symptoms, depression, and school dropout rates. The age of 6-9 years is a period of transition in exploratory learning and playing to formal schooling with exams so that this age is vulnerable to early stress. The activity of reading books that children and parents do can provide a sense of comfort, thereby reducing children's stress. Picture books are believed to be related to the formation of children's character, introduce concepts, and have a positive impact on the world of children. The visual narrative implied in the picture book can be a visual approach that attracts children. Until now, there has not been much research discussing visual narrative stress management for children aged 6-9 years. Research on book design using a visual narrative approach to introducing stress management as an alternative solution to problems needs to be carried out and studied. This study aims to design a visual narrative strategy that is implemented in a picture book illustration with the theme of stress management. This study uses a qualitative approach with literature studies, document studies, observations, and interviews to design the visual narrative’s strategy. The finding is that a visual narrative approach of contradiction, metaphor, and humor in children's books can be a illustration approach that provides comfort and a relaxing effect with easy-to-see illustrations.